Analysis of Employee Turnover Intention at Indriati Hospital Solo Baru Sukoharjo - Angga Arinda Tri Murti Nugroho; Istiatin Istiatin; Yunus Yunus (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to find the influence of career development, work stress, job satisfaction, burnout on turnover intention. Data This type of research uses quantitative methods. This study is a survey study conducted on medical employees of Indriati Solo Baru Sukoharjo Hospital. This research was conducted at Indriati Solo Baru Sukoharjo Hospital. Jl. Palem Raya, Dusun III, Langenharjo, Solo Baru, Sukoharjo Regency, Central Java 57552. The reason for the research at this location is that there has been no research on employee turnover intention conducted at Indriati Solo Baru Sukoharjo Hospital. This study was conducted for 6 months, namely in June 2025 - November 2025. The population of this study were medical employees, namely nurses at Indriati Solo Baru Sukoharjo Hospital, totaling 320 nurses. The sample in this study were employees who had completed Bachelor of Nursing Education, namely 80 employees. Sampling in this study used a purposive sampling technique. The primary data in this study were obtained from questionnaires on career development, job stress, job satisfaction, burnout, and turnover intention. Secondary data were obtained from research journals related to the study.Based on the results of hypothesis testing and the discussion that has been conducted, it can be concluded that career development has a negative and significant effect on employee turnover intention at Indriati Hospital, Solo Baru, Sukoharjo. Work stress has a positive and significant effect on employee turnover intention at Indriati Hospital, Solo Baru, Sukoharjo. Job satisfaction has a negative and significant effect on employee turnover intention at Indriati Hospital, Solo Baru, Sukoharjo. Burnout has a positive and significant effect on employee turnover intention at Indriati Hospital, Solo Baru, Sukoharjo.